2006
DOI: 10.1359/jbmr.060303
|View full text |Cite
|
Sign up to set email alerts
|

HES1 Cooperates With pRb to Activate RUNX2-Dependent Transcription

Abstract: The retinoblastoma protein, pRb, can activate the transcription factor RUNX2, an essential regulator of osteogenic differentiation, but the mechanism of this activation is unknown. Here we studied the interaction of pRb and RUNX2 with HES1, previously reported to augment RUNX2 activity. PRb can act to promote RUNX2/HES1 association with concomitant promoter occupancy and transcriptional activation in bone cells.Introduction: RUNX2 (also known as OSF2/CBFA1) is a transcription factor required for osteoblast dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 58 publications
(142 reference statements)
2
43
0
Order By: Relevance
“…On the contrary, Lee and colleagues recently reported that Hes1, which is another downstream transducer of Notch1 signaling, stimulated Runx2 activity by cooperating with retinoblastoma protein (pRb). (51) Furthermore, Jung and colleagues reported that Hes1 overexpression led to an increase in osteoblast differentiation, presumably resulting from enhanced Runx2 activity elevating Runx2 target gene expression. From cDNA microarray data it was shown that Notch1, Notch3, and NOV genes are downregulated but Hey1 is upregulated during osteoblast differentiation of MC3T3 cells, suggesting that Hey1 is a BMP-2-induced gene through a Notch1-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Lee and colleagues recently reported that Hes1, which is another downstream transducer of Notch1 signaling, stimulated Runx2 activity by cooperating with retinoblastoma protein (pRb). (51) Furthermore, Jung and colleagues reported that Hes1 overexpression led to an increase in osteoblast differentiation, presumably resulting from enhanced Runx2 activity elevating Runx2 target gene expression. From cDNA microarray data it was shown that Notch1, Notch3, and NOV genes are downregulated but Hey1 is upregulated during osteoblast differentiation of MC3T3 cells, suggesting that Hey1 is a BMP-2-induced gene through a Notch1-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additionally, Hes1 increases Runx2-DNA binding, stimulates Runx2 transcriptional activity by increasing the stability of Runx2, and associates with pRb synergistically to augment Runx2 transcription. 42,43 When examined in prostate tumor bone metastasis, Runx2 DNA-binding activity is enhanced in response to osteogenic induction and is inhibited by Notch-Hes1 inhibition, verifying that Hes1-Runx2 signaling functions critically in tumor bone metastasis. 44 Furthermore, EMT process allows the loss of junction with adjacent cells, the polarization of epithelial cells and subsequent acquisition of mesenchymal features.…”
Section: Overview Of Hes1 Factormentioning
confidence: 95%
“…Hes1 amplifies Runx2 expression by cooperating with pRb, and WRPW domain is necessary for Hes1-pRb interacion. 42 In addition, Hes1 uses bHLH domain and orange domain to bind with STAT3 and activates STAT3 phosphorylation. 58 The role of Hes1 in CSCs maintenance Hes1 is widely expressed in different tissue and cell types, including neuronal stem cells, embryonic stem cells, quiescent cells, and especially in cells at the precursor stage.…”
Section: Overview Of Hes1 Factormentioning
confidence: 99%
“…(9) Among the cofactors that interact with Runx proteins are coactivators such as p300 and CREB-binding protein (CEBP) and co-repressors such as mSin3A, transducin-like enhancer of split proteins (TLEs), and several histone desacetylases (Hdacs). Several RUNX2 responsive elements have been identified in important bone-related genes, such as osteocalcin, (10)(11)(12)(13)(14)(15)(16) osteoprotegerin, (17) osterix, (18) and bone sialoprotein, (19)(20)(21) among others. More interestingly, functional RUNX2 binding sites have been described in the promoters of genes of other Wnt signaling pathway elements, such as SOST (22) and AXIN2 genes.…”
Section: Introductionmentioning
confidence: 99%